Enhanced fluorescence of aqueous BODIPY by interaction with cavitand cucurbit[7]uril. Issue 4 (9th December 2016) - Gupta, Monika; Parvathi, K.; Mula, Soumyaditya; Maity, Dilip K.; Ray, Alok K.
Abstract : Host–guest interactions of the host cucurbit[7]uril (CB[7]) with a water soluble cationic BODIPY dye2 are scarcely reported. Abstract : One cationic BODIPY chromophore was synthesized and its complexation behaviour with the macrocyclic host cucurbit[7]uril (CB[7]) was studied using different spectroscopy techniques such as UV-vis absorption, steady-state and time-resolved fluorescence, 1 H NMR as well as DFT based quantum calculations. The dye showed formation of a 1 : 1 dye–CB[7] complex with improvement in the fluorescence intensity. These new results of the formation of moderate association of aqueous BODIPYs with the nontoxic host CB[7] may lead to promising applications of the dye molecule as a sensitive and efficient off–on mode fluorescent probe in chemical and biological studies.